Drinking water disinfection techniques - Pandit, Aniruddha Bhalchandra; Kumar, Jyoti Kishen (Boca Raton, CA. : CRC Press, 2013)
'This book effectively combines the chemical, physical, biological and engineering principles of water disinfection in one text. Discussing both conventional and novel techniques used for disinfection and the economics involved, the book gives a comprehensive review of various physical, chemical, and hybrid techniques used for disinfection to create potable water, including mode of action, scale of operation, efficacy, merits, and drawbacks. The authors highlight their novel work on cavitation for water disinfection, an economical, energy efficient, and simple alternative to the conventional methods of disinfection'--
Includes bibliographical references and index.
Keywords: Drinking water -- Purification